A new species of Pontarachna (Acari, Hydrachnidia, Pontarachnidae) from a mesophotic coral ecosystem off Vieques Island, Puerto Rico, Caribbean Sea - Pešić, Vladimir; Chatterjee, Tapas; Schizas, Nikolaos V. (Zootaxa, 2012)
The water mite family Pontarachnidae Koenike, 1910, the only family of the Hydrachnidia occurring in the marine environment, represents a diverse and widespread, but still neglected group of marine meiofauna. Most marine species live nearshore with the exception of few freshwater species found in estuaries or locations near the sea (Smit 2002; Smit & Alberti 2010). In this paper we describe a new species, Pontarachna nemethi, from substrata collected from El Seco, a mesophotic site near Vieques Island off Puerto Rico, from 52–67 m depth, more than 2 times the depth at which Pontarachnidae have been previously collected. The finding of the new species remarkably extended the potential area of the world ocean occupied by the Pontarachnidae.